Drain catheter-induced urinary bladder fistula: A rare complication following exploratory laparotomy for duodenal ulcer - Ahmed, Omer Hamza Ali; Subahi, Reem Mubark Abdelrheem; Alameen, Fatin Abdelmoneim Omer; Khalafalla, Abdelazim Hussein; Obaid, Mohamed Obaid Mohamed (Indian Journal of Case Reports, 2025)
Pelvic drains are commonly used in abdominal surgeries to prevent fluid accumulation, identify post-operative complications, and allow early detection of anastomotic leakage. We report a rare case of a 35-year-old male who developed a urinary bladder fistula a few days after exploratory laparotomy for a perforated duodenal ulcer. The patient initially presented with generalized abdominal pain, fever, and peritonitis. Imaging confirmed pneumoperitoneum, and an emergency laparotomy revealed a perforated duodenal ulcer. A right subhepatic drain and a pelvic drain were placed. On post-operative day 5, the pelvic drain output increased and resembled urine. Further imaging revealed that the drain tip had entered the bladder, causing a fistula. Conservative management with urethral catheterization and drain repositioning was successful. This case highlights the importance of vigilance during drain placement, awareness of risk factors such as prolonged drain retention, and early recognition of atypical drain output. It also underscores the role of conservative management in selected cases.